Chemical Extractive Technique for Commercial Purity Metals - Mustafa, Ali Mundher (Al-Nahrain Journal for Engineering Sciences, 2018)
Commercial purity iron powders were produced by using a new hydrometallurgy process. It was found that the most important factor in enhancing the purity of iron was the number of water washing process. X-ray diffraction pattern showed that the high peak purity of iron powder increased with increasing the number of water washing. The developed new methodology was based on the reaction between the aqueous ferrous sulfate and the hydrochloric acid with the presence of high purity aluminum flake. The purity of iron powders increased considerably with increasing the multi-water washing for leachate containing iron powders. The purity of iron powders was reached up to approximately 93.5%. The mean particle size distribution and apparent density for the highest value of purity are 50-100 µm and 2.85 g/cm3 respectively.